New insights in the history of interpreting - 武田, 珂代子; Baigorri Jalón, Jesús (Benjamins Translation Library, 2016)
Who mediated intercultural exchanges in 9th-century East Asia or in early voyages to the Americas? Did the Soviets or the Americans invent simultaneous interpreting equipment? How did the US government train its first Chinese interpreters? Bringing together papers from an international symposium held at Rikkyo University in 2014 along with two select pieces, this volume pursues such questions in an exploration of the practice of interpreting, the recruitment of interpreters, and the challenges interpreters have faced in diplomacy, colonization, religion, war, and occupation. It also introduces innovative use of photography, artifacts, personal journals, and fiction as tools for the historical study of interpreters and interpreting. Targeted at practitioners, scholars, and students of interpreting, translation, and history, the new insights presented aim to spark discussion and research on the vital roles interpreters have played in intercultural communication through history.